Archival classification by processes: an experience in the University of Havana. - Guirola Benkí, Sissy Laura; Neyda Batista Delgado, Adiela; Herrera Acosta, Reina Estrella (Revista General de Información y Documentación, 2016)
The purpose of this paper is to analyze the new trends in document classification practices and expose a proposed classification scheme by processes of the Summer School of the University of Havana. This research analyzed the documents generated by the Summer School and their functions, and also their context of creation. It is concluded that even when the process approach in the discipline of organizational management is well defined, in the Document Management is a stand construction that does not yet have a precise theoretical basis, making it difficult to establish the boundaries between the traditional Document Management and the Document Management by processes. The investigation materialize in the practice of Document Management focused on processes, which are fundamental archival tools that record the production of documents.